Rheometric Studies of New Class Ionic Liquid Nanolubricants - Siginer, D (American Society of Mechanical Engineers, 2017)
The traditional lubricating materials used in space, such as mineral oils, polyol ester, PFPE, Pennzane, etc. have limited lifetimes in vacuum due to the catalytic degradation on metal surfaces, high vaporization at high temperatures, dewetting, and other disadvantages. The lubricants for the space applications must have vacuum stability (i.e. low vapor pressure), high viscosity index (wide liquid range), low creep tendency, good elastohydrodynamic and boundary lubrication properties, radiation atomic oxygen resistance, optical or infrared transparency. Thermophysical and chemical analyses are another important required set of tests for the newly developed space lubricants. Some of these properties for liquid lubricants are base oil and additive volatility, creep, surface tension, viscosity, chemical composition, weight loss, density, vapor pressure, etc. Unfortunately, the properties such as non-linearity in the rheological behavior of the lubricants were not studied well for newly developed systems. The rheological properties are crucial to analyzing thermodynamic and energy dissipative aspects of the lubrication process. The rheological measurements for the newly developed ionic liquid nanolubricant were conducted using rotational rheometer AES G-2 of "parallel-plates" mode. Copyright © 2017 ASME.